1941
DOI: 10.1021/ja01853a008
|View full text |Cite
|
Sign up to set email alerts
|

Alkyl Carbonates in Synthetic Chemistry. I. Condensation with Organic Esters. Synthesis of Malonic Esters1

Abstract: Compared to other simple organic esters, the alkyl carbonates have found little application in synthetic reactions. This is the first of several papers reporting investigations which greatly extend the uses of this interesting class of compounds. Scattered through the literature may be found a few instances in which alkyl carbonates have been employed but none of these suggests a type reaction of broad applicability or utility.The present paper describes a method of condensing alkyl carbonates with organic est… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
11
0

Year Published

1973
1973
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(11 citation statements)
references
References 0 publications
0
11
0
Order By: Relevance
“…At the same time, diethyl 2-(perfluorophenyl)malonate ( 3 ) is a readily accessible compound. Diethyl 2-phenylmalonate ( 4 ) is usually obtained ( Scheme 1 ) by condensation of ethyl phenylacetate ( 5 ) and diethyl carbonate under basic conditions [ 22 ] because of the low reactivity of bromobenzene in noncatalytic nucleophilic reactions with sodium salts of diethyl malonate ( 6 ) [ 23 24 ].…”
Section: Resultsmentioning
confidence: 99%
“…At the same time, diethyl 2-(perfluorophenyl)malonate ( 3 ) is a readily accessible compound. Diethyl 2-phenylmalonate ( 4 ) is usually obtained ( Scheme 1 ) by condensation of ethyl phenylacetate ( 5 ) and diethyl carbonate under basic conditions [ 22 ] because of the low reactivity of bromobenzene in noncatalytic nucleophilic reactions with sodium salts of diethyl malonate ( 6 ) [ 23 24 ].…”
Section: Resultsmentioning
confidence: 99%
“…Reaction of 2-amino-3-carbamoyl-5-phenylpyrazine 1-oxide with ethyl chloroformate in xylene solution, as described above, gave 2-ethoxycarbonylamino-3-carbamoyl-5-phenylpyrazine 1-oxide (8b) (84% yield), which was cyclized to 6-phenyllumazine 8-oxide by heating with sodium methoxide in methanol: yield, 90%, mp >320°; nmr (CFsCOOH) 7. 30 (3, m), 8.00 (2, m, C6-C6H5), 8.93 (1, s, Cr-H); uv X"2°nm…”
Section: Experimental Section32mentioning
confidence: 99%
“…We therefore attempted to repeat the potentiometric titration on a very pure sample of 2,2,6,6-tetramethylpiperid-4-one N-oxyl. 30 There was no break in the titration curve from pH 8 to 2 and the nitroxide still gave a strong epr signal. It must be concluded that Rozantsev and Gintsberg titrated an impurity.…”
mentioning
confidence: 94%
“…Scheme 1A). [6] To address these issues, a greener alternative is the carboxymethylation reaction using (i) environmental friendly reagents and (ii) heterogeneous catalysts.…”
mentioning
confidence: 99%
“…Unfortunately, the currently applied routes toward these chemicals rely on toxic reagentse.g. chloroformates, trimethylamine, pyridine, phosgeneand on the use of homogeneous catalysts, which are non-reusable and require onerous separation procedures (Scheme A) . A greener alternative would be carboxymethylation reactions using (i) environmentally friendly reagents and (ii) heterogeneous catalysts.…”
mentioning
confidence: 99%